Awake prone positioning of hypoxaemic patients with COVID-19: protocol for a randomised controlled open-label superiority meta-trial. Issue 11 (11th November 2020) - Tavernier, Elsa; McNicholas, Bairbre; Pavlov, Ivan; Roca, Oriol; Perez, Yonatan; Laffey, John; Mirza, Sara; Cosgrave, David; Vines, David; Frat, Jean-Pierre; Ehrmann, Stephan; Li, Jie
Abstract : Introduction: Prone positioning (PP) is an effective first-line intervention to treat patients with moderate to severe acute respiratory distress syndrome (ARDS) receiving invasive mechanical ventilation, as it improves gas exchanges and reduces mortality. The use of PP in awake spontaneous breathing patients with ARDS secondary to COVID-19 was reported to improve oxygenation in few retrospective trials with small sample size. High-level evidence of awake PP for hypoxaemic patients with COVID-19 patients is still lacking. Methods and analysis: The protocol of this meta-trial is a prospective collaborative individual participant data meta-analysis of randomised controlled open label superiority trials. This design is particularly adapted to a rapid scientific response in the pandemic setting. It will take place in multiple sites, among others in USA, Canada, Ireland, France and Spain. Patients will be followed up for 28 days. Patients will be randomised to receive whether awake PP and nasal high flow therapy or standard medical treatment and nasal high flow therapy. Primary outcome is defined as the occurrence rate of tracheal intubation or death up to day 28. An interim analysis plan has been set up on aggregated data from the participating research groups. Ethics and dissemination: Ethics approvals were obtained in all participating countries. Results of the meta-trial will be submitted for publication in a peer-reviewed journal. Each randomised controlled trial was registered individually, as follows: NCT04325906, NCT04347941, NCT04358939, NCT04395144 and NCT04391140 .